Peculiarities of developing logistic business processes in modern conditions - S. M. Khairova; S. V. Potapova (Вестник СибАДИ)
The authors have investigated the main tendencies and factors of developing logistic bisiness-processes and forms of the organization of logistic service. There are revealed peculiarities of logistic management in modern conditions. There is considered a methodical approach to the reliability’s assessment and problems of controlling supply chains are defined.